1980
DOI: 10.1073/pnas.77.7.4270
|View full text |Cite
|
Sign up to set email alerts
|

kappa Chain joining segments and structural diversity of antibody combining sites.

Abstract: Immunoglobulin K light chains are coded for by at least three distinct gene segments designated variable, joining, and constant. The joining gene codes for the 13 amino acid segment linking the variable and constant regions. This peptide includes the last amino acid (96) in the third complementarity-determining region and thus could introduce structural diversity. We have determined the light chain variable region sequences from three myeloma proteins with P(1,6)galactan-binding specificity, bringing to six th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
21
0

Year Published

1981
1981
2017
2017

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 43 publications
(21 citation statements)
references
References 22 publications
0
21
0
Order By: Relevance
“…Fourth, the presence of a positively charged center to the antigen-binding pocket, provided by the side chain of arginine L96, and surrounded by an aromatic area and a ridge of polar residues, would imply that a negatively charged or electron-rich group exists in the epitope interactive with these BCRs (Figure 3). This, however, is not a necessity (41,53,59). Of the 199 completely sequenced antibodies with an arginine at L96 (14), we found that about 50% react with autoantigens.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…Fourth, the presence of a positively charged center to the antigen-binding pocket, provided by the side chain of arginine L96, and surrounded by an aromatic area and a ridge of polar residues, would imply that a negatively charged or electron-rich group exists in the epitope interactive with these BCRs (Figure 3). This, however, is not a necessity (41,53,59). Of the 199 completely sequenced antibodies with an arginine at L96 (14), we found that about 50% react with autoantigens.…”
Section: Discussionmentioning
confidence: 93%
“…Murine mAb's reactive with arsonate (Ars), dsDNA, and β-(1,6)-D-galactan exhibit an arginine or an isoleucine at position L96, respectively. These junctional amino acids are essential for binding to Ars (53), but not to β-(1,6)-D-galactan (59).…”
Section: Discussionmentioning
confidence: 99%
“…14) had not been reported in A chains. This detection Rudikoff et al (33) that the V-J boundary residue of K chains was a direct consequence of analysis of X chain contributions has no significant effect on hapten binding. They found that to ligand-binding activity.…”
mentioning
confidence: 99%
“…One such system being developed in our laboratory consists of antibodies with specificity for/3(1,6)-a-galactan moieties. A number of myeloma proteins demonstrating this specificity were initially characterized in terms of specificity (38,40), idiotypy (41), and primary sequence analysis (10,19). More recently we have generated a series of hybridoma proteins exhibiting the same specificity and have reported complete r chain V region sequences for 10 of these (37).…”
Section: Resultsmentioning
confidence: 99%